Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10815-015-0600-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of follicle-stimulating hormone receptor Asn680Ser polymorphism on the outcomes of controlled ovarian hyperstimulation: an updated meta-analysis of 16 cohort studies

Abstract: FSHR Asn680Ser polymorphism might be a significant biomarker for predicting the number of retrieved oocytes and poor response, especially in Asian subjects. Other outcomes such as exogenous FSH dose, OHSS, and pregnancy rate were not influenced by FSHR Asn680Ser polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
3
21
1
Order By: Relevance
“…We additionally assessed the ovarian response to COS as well as the time and amount of gonadotrophins required to reach a mean follicle diameter of 18 mm in normal oocyte donors and infertile patients from the IVF group bearing different N680S FSHR variants. Despite the low number of oocyte donors with the GG genotype, we consistently detected an association of this genotype with a lower number of oocytes retrieved after gonadotrophin administration, thus confirming previous studies on the effect of the S680S phenotype on the ovarian sensitivity and response to exogenous FSH administration [ 6 , 7 , 15 17 , 44 46 ]. The lower number of oocytes retrieved in donors with the GG genotype was not apparent in the infertile women, finding that may be due to the age-dependent vanishing effect of the N680S polymorphism on the ovarian response to COS, as previously suggested [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…We additionally assessed the ovarian response to COS as well as the time and amount of gonadotrophins required to reach a mean follicle diameter of 18 mm in normal oocyte donors and infertile patients from the IVF group bearing different N680S FSHR variants. Despite the low number of oocyte donors with the GG genotype, we consistently detected an association of this genotype with a lower number of oocytes retrieved after gonadotrophin administration, thus confirming previous studies on the effect of the S680S phenotype on the ovarian sensitivity and response to exogenous FSH administration [ 6 , 7 , 15 17 , 44 46 ]. The lower number of oocytes retrieved in donors with the GG genotype was not apparent in the infertile women, finding that may be due to the age-dependent vanishing effect of the N680S polymorphism on the ovarian response to COS, as previously suggested [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…The quality of the included studies was assessed by 2 reviewers independently through a checklist derived from the Strengthening the Reporting of Genetic Association (STREGA) recommendations for reports on genetic association studies [16], which was widely employed in previous meta-analysis studies [17,18].…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…FSHR overexpression may play a role in the early phase of EOC development [ 29 ]. However, the majority of studies are inconsistent and inconclusive results [ 8 , 15 , 30 ]. Our study showed the expression levels of FSHR mRNAs and proteins of FRBI-treated groups less than CG and FSH group.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP and IP3 further lead to the activation of the downstream cascade of protein kinases. FRBI is able to fully inhibit FSH-induced cAMP production, thereby inhibiting steroidogenesis [ 30 ]. Up to date, whether FRBI treatment of oocytes influences this signal transduction remains unknown [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%